2021
DOI: 10.3389/fphar.2021.644225
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Attenuates Lipopolysaccharide-induced Apoptosis by Regulating the Cx43/PI3K/AKT Pathway

Abstract: Cardiomyocyte apoptosis is a crucial factor leading to myocardial dysfunction. Adiponectin (APN) has a cardiomyocyte-protective impact. Studies have shown that the connexin43 (Cx43) and phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT) signaling pathways play an important role in the heart, but whether APN plays a protective role by regulating these pathways is unclear. Our study aimed to confirm whether APN protects against lipopolysaccharide (LPS)-induced cardiomyocyte apoptosis and to explore whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…The mice were housed in constant temperature (24°C ± 2°C) and humidity (50-60%) under a 12-h light/dark cycle with free access to standard food and water. Mice were randomly divided into four groups as follows: control (Ctrl group), neferine (Nef group), septic myocardial injury (LPS group), and neferine combined with LPS (LPS + Nef group).To establish the septic myocardial injury model, mice were intraperitoneally injected with 10 mg/kg LPS (Liu et al, 2021). In the Ctrl group, the same amount of normal saline was injected intraperitoneally.…”
Section: Animalsmentioning
confidence: 99%
“…The mice were housed in constant temperature (24°C ± 2°C) and humidity (50-60%) under a 12-h light/dark cycle with free access to standard food and water. Mice were randomly divided into four groups as follows: control (Ctrl group), neferine (Nef group), septic myocardial injury (LPS group), and neferine combined with LPS (LPS + Nef group).To establish the septic myocardial injury model, mice were intraperitoneally injected with 10 mg/kg LPS (Liu et al, 2021). In the Ctrl group, the same amount of normal saline was injected intraperitoneally.…”
Section: Animalsmentioning
confidence: 99%
“…Yang et al found that LPS (10 μg/ml) reduced the expression of p-eNOS in human pulmonary microvascular endothelial cells (HPMECs) ( Yang et al, 2018 ). Liu et al found that p-AKT was markedly suppressed in H9c2 cells after treatment with LPS (1 μg/ml) for 24 h ( Liu et al, 2021 ). The effect of LPS on AKT expression in out study was consistent with the study of Li et al and Zhan et al Li et al showed that there was no significant change in AKT expression of LPS-induced (20 μg/ml) mouse microvascular ECs ( Li H. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that this process is one of the earliest events in the apoptosis cascade and occurs before the changes in the nucleus (chromatin concentration, DNA fragmentation), and once this change occurs, cell apoptosis is irreversible ( 56 ). The PI3K/AKT/mTOR signaling pathway plays an important role in apoptosis ( 57 ). We found that DHW-208 could significantly inhibit the proliferation of Hep3B and Bel7402 HCC cells and promote HCC cell apoptosis by inducing the endogenous apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%